Photoluminescence study of cadmium telluride films by vacuum evaporation - Foo, Lai Tee, 1987-; Bakar Ismail, supervisor; Fakulti Sains (2010)
Project paper (Sarjana Muda Sains Industri (Fizik Bahan)) - Universiti Teknologi Malaysia, 2010